Legal Construction for the Establishment of Sharia Economic Special Courts in Religious Courts in Indonesia - Saut Maruli Tua Manik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The urgency of establishing a special sharia economic court within the Religious Courts is due to the dualism of sharia economic dispute settlement institutions that still continues due to the harmonization of laws and regulations related to sharia economics has not been carried out. The purpose of this study is to analyze the legal construction of the establishment of a special sharia economic court in the religious courts in Indonesia, and the important factors in the establishment of a special sharia economic court in the religious courts in Indonesia. The normative method is used in research with a normative juridical approach. The results of the study are the legal construction of the establishment of a special sharia economic court placed within the Religious Courts and culminating in the Supreme Court of the Republic of Indonesia. The establishment of a special sharia economic court is constitutionally based on Article 24 paragraph (2) of the 1945 Constitution, the provisions of Article 1 paragraph 8 and Article 27 paragraph (1), paragraph (2) of Law Number 48 of 2009 concerning Judicial Power and Article 3A of the Law Number 3 of 2006, affirmed Article 3A paragraphs (1), (3) and 13B paragraph (1) of Law Number 50 of 2009 concerning the Second Amendment to Law Number 7 of 1989 as the legal basis.